2021
DOI: 10.1186/s12891-021-04844-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving effect of microendoscopic decompression surgery on low back pain in patients with lumbar spinal stenosis and predictive factors of postoperative residual low back pain: a single-center retrospective study

Abstract: Background Although there are reports on the effectiveness of microendoscopic laminotomy using a spinal endoscope as decompression surgery for lumbar spinal stenosis, predicting the improvement of low back pain (LBP) still poses a challenge, and no clear index has been established. This study aimed to investigate whether microendoscopic laminotomy for lumbar spinal stenosis improves low back pain and determine the preoperative predictors of residual LBP. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Preoperatively, LBP-VAS is considered a predictor of leg numbness after spinal endoscopic surgery. Taiji et al showed the leg numbness VAS to be as high as 61.4 to 65.2 in patients with lower back pain after endoscopic spinal surgery [ 11 ]. A multiple logistic regression study also showed preoperative lower back pain to be a risk factor (OR = 2.19) for postoperative lower back pain [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Preoperatively, LBP-VAS is considered a predictor of leg numbness after spinal endoscopic surgery. Taiji et al showed the leg numbness VAS to be as high as 61.4 to 65.2 in patients with lower back pain after endoscopic spinal surgery [ 11 ]. A multiple logistic regression study also showed preoperative lower back pain to be a risk factor (OR = 2.19) for postoperative lower back pain [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taiji et al showed the leg numbness VAS to be as high as 61.4 to 65.2 in patients with lower back pain after endoscopic spinal surgery [ 11 ]. A multiple logistic regression study also showed preoperative lower back pain to be a risk factor (OR = 2.19) for postoperative lower back pain [ 11 ]. A herniated disc destroys the annulus fibrosus, releasing chemicals that irritate the sinus nerve and cause lower back pain [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lumbar spinal stenosis (LSS) is a condition in which the dural tract and the nerve roots are compressed due to the degeneration of the intervertebral disk, and facet joints. This leads to the thickening/buckling of ligamentum flavum (1). The first clinical description was attributed to Verbiest in 1954.…”
Section: Introductionmentioning
confidence: 99%